Equivalence of online and clinician administration of a patellar tendinopathy risk factor and severity questionnaire. Issue 5 (21st November 2014) - Morton, S.; Morrissey, D.; Valle, X.; Chan, O.; Langberg, H.; Malliaras, P.
Abstract : The VISA‐P is a questionnaire for assessing the severity of patellar tendinopathy (PT). Our study aim was to evaluate the equivalence of self‐administration of the VISA‐P online with the addition of risk factor questions to develop a tool suitable for high‐volume remote use. A crossover study design with 107 subjects was used to determine equivalence between online and clinician administration. Three population groups were used to ensure construct validity. Online vs clinician administration revealed an intraclass correlation (ICC) of 0.79 [confidence interval (CI): 0.68–0.86] for the VISA‐P with a systematic significant difference of 4.99, which is not clinically meaningful. Poor ICCs were seen for questions 7 and 8 of the VISA‐P (0.37 and 0.47, respectively) in comparison with earlier questions. There were statistically significant differences between population groups for the VISA‐P. The ICC for risk factor questions was excellent at 0.89 (CI: 0.84–0.93) with no mean difference ( P = 1.00). The online questionnaire enables equivalent collection of VISA‐P data and risk factor information and may well improve further with the suggested modifications to the instructions for questions 7 and 8. There is potential to use this questionnaire electronically to generate large databases in future research.